GENDER GENEALOGY OF READING AS CULTURAL PRACTICE - N. Yu. Kryvda; L. V. Osadcha (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The article is devoted to the cultural aspect of texts using in European culture. The paper found out methodological basis of correctly interpreting the term "practice" in the philosophical and sociological discourses. In the first case the concept reveals human nature; appealing to the field of ethics and intersubjective interactions. In sociological approach the term practice is contrasted to institutional life. It seems to be an organic; vital relevance of actions for contrast to the mechanically regulated community life. Methodology. The paper considered the typology of human intellectual conditions according to Kant’s divided into pure and practical reason. The last one directs action-willed individual efforts so as to meet the universal relevance and ethical coherence. Gottlieb Fichte interpreted practice reason as the way to combine intellectual intentions and material conditions of human being. G. W. F. Hegel enriched the concept with terms of "objectification" and "alienation” of labour. Karl Marx formulated the main features of activity approach to the human nature exploring. In sociological discourse the term practice is opposed to mechanically done actions (according to institutional normativity). Given the philosophical and sociological methodological contexts the reading is studied as activity that aimed emotional and volitional contact with sense. Originality. The paper analysed the genealogy of reading practices. There were selected two types of text perception – rapid "masculine" and prudent "women's" reading. Women salon environment of the XVIII-th century capitalistic Europe was the main condition for the forming of literary-aware public. The authors analysed the process of reading of the text-as-satisfaction and text-as-pleasure (R. Barthes). The work presents the overview of classical studies of sociocultural field: Thorstein Veblen; Vladimir Toporov; Rolan Barthes and contemporary researchers such as T. Markova (2013); A. Smahtinova (2015); B. Jack (2013); D. G. Scott (2015); R. A. Fullerton (2016). Conclusions. The practice of thoughtful reading connects the subject with culture; makes a man coeval to any historical era. Using the text; a person faces the cultural meanings without any institutional mediation; thus forming self-identity.